Effect of the Use of English Language in Children's Cartoons on the Improvement of English Language Skills in 10-Year-Old Children ( 5th Grade Elementary School) - Ilmi, Khoirotul; Mahmudah, Nailuz Zakiyatul; Hadiwijaya, Munawwir (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This article discusses the effect of the use of English in children's cartoons on the improvement of their English language skills. Children's cartoons are often an important part of children's daily lives, and the use of English in these cartoons can have a significant impact on their language development. In this article, we conducted research to evaluate whether the use of English in children's cartoons can improve their english speaking skills. The research method used involves collecting data from a number of children who were exposed to English-language cartoons over a certain period. The results of the study show that the use of English in children's cartoons has a positive influence on the improvement of their English language skills. Children exposed to English-language cartoons consistently showed improvements in terms of vocabulary, pronunciation, and comprehension of English. In addition, this article also discusses several factors that affect the effectiveness of the use of English in children's cartoons. These factors include the quality of the cartoon material, the variety of topics presented, and the use of appropriate learning strategies. In conclusion, this article shows that the use of English in children's cartoons has a positive influence on the improvement of their English language skills. Therefore, it is recommended that parents and teachers choose cartoons with good and useful English to help children improve their English skills.